SIKAP SISWA SEKOLAH DASAR TERHADAPPENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN - Esti Widayati (Jurnal Pendidikan Jasmani Indonesia, 2013)
This study aims to determine the attitude of elementary school students to sports and health education, involvinglike or dislike and favorite order of the twelve areas of study in the Elementary School. Population of elementary schoolstudents Keputran 1, 2 Keputran Primary School, Primary School A and School Keputran Kraton basis, a sampleof 400 students from each school consisted of 100 respondents with a composition of 50 sixth grade students, 30fifth grade students and 20 fourth grade students. Comparison of 50 % female students and 50 % male students.Random sampling technique and proportional (proportional random sampling ). Research instrument in the form ofa questionnaire which is a mixed open. results closed questionnaire and questionnaire research showed that thePhysical Education Health Sports ranks 1 out of 12 students preferred field of study that is in elementary school.The attitude of the students stated that 130 students (34 %) stated thrilled and 196 students (53 %) felt happy, feltnormal 50 students (13 %). Students are happy to justify the benefits of Physical Education Sports Health for healthreasons (43 %) as in outer space free (22 %) , close student-teacher relationship (13 %), the material is not a lot ofthinking (26 %), while learning playing around quipped (17 %), want to see famous athletes (18 %), the reason othersinclude: making new friends , see the sights outside (10 %). On the abolition of primary school curriculum sports andhealth education of 361 students (96 %) disagreed, 12 students (3 %) of the unaware, 1 student (0.03 %) disagreeand 4 students (0.97 %) corrupted data. Students' opinions about the presentation sports and health education 260students (69 %) blend of theory and practice in a room outside the room, 99 students (26 %) only requires practice,4 students (1 %) require only a theory, 9 students (2.4 %) did not answer and 6 students (1.6 %) of the indifferent.Keywords: Attitude, Elementary Students, Sports And Health Education.